Understanding the contributing factors and the barriers prohibiting successful implementation of smart cities in Africa - Bingandadi, Mutsa (Department of Construction Economics and Management, 2025)
Africa is a rapidly developing continent with immense potential. Several “Smart solutions” or “Smart Cities” have been initiated at various scales and with different ethos's. The Smart City concept has been proposed as a solution that aims to aid in solving some of the socio-economic problems that are currently being faced in the different contexts on the continent. What is important to consider and understand is how these developments have fared and understand the barriers and contributing factors to the different results that have been produced. This research used interviews from different perspectives from subjects who have knowledge of or have been involved with Smart Cities to uncover the barriers and contributing factors to smart city implementation on the continent. Themes were uncovered in the literature that the interviews tested to prove or disprove the research proposition made. The research proved the proposition to be true. Various socio-economic issues have hindered the execution and progression of the smart city concept in the selected African cities analysed. Literature has noted smart cities as a potential aid in combating rapid urbanisation and the research corroborated this claim. The research determined that urbanisation can be looked at from different perspectives and that innovative solutions regarding transport, the economy and housing will contribute to positive reactions to urbanisation. Governance served to be a multi-faceted issue. Governance relates to the level of understanding of the smart city concept that staff in decision-making decisions have and their ability to implement the concepts that are relevant. The research uncovered that a lack of understanding led to the reluctance of implementing smart solutions and the lack of robust systems meant that the operations taking place during the development and running of smart solutions were often sub-optimal. This brought into question the design considerations that have been made in the smart solutions that have been designed and implemented. The research determined that there have been holistic considerations when designing smart cities and solutions to consider all the facets of an urban space that are relevant and constitute as “smart solutions”. Additionally, the research identifies the design considerations are contextual to the application and serve to solve some of the issues that currently exist and have been forecasted. Ultimately, the success of these projects and the project success criteria determines the value system and the direction that the project will take, and the research illustrated congruency between the projects and literature. Smart city project success criteria, from the research, can be seen as the fulfilment of people/user-centric solutions that is tangibly felt by the integration and usage of the solutions provided. Finally, the research recommended that improved stakeholder engagement will create a foundation with better direction for the development of smart cities. Additionally, governing bodies should task themselves to do the following: review and overhaul the old systems they're currently looking to use in new applications, understand the smart city concept in its most ideal form for application, pivot to use more innovative solutions that may be more productive than the outdated solutions they have attempted to use in the past.